Therapeutic Potential of Retinoid X Receptor Modulators for the Treatment of the Metabolic Syndrome - Jane A. Pinaire; Anne Reifel-Miller (PPAR Research)
The increasing prevalence of obesity is a fundamental contributor to the growing prevalence of the metabolic syndrome. Rexinoids, a class of compounds that selectively bind and activate RXR, are being studied as a potential option for the treatment of metabolic syndrome. These compounds have glucose-lowering, insulin-sensitizing, and antiobesity effects in animal models of insulin resistance and type 2 diabetes. However, undesirable side effects such as hypertriglyceridemia and suppression of the thyroid hormone axis also occur. This review examines and compares the effects of four RXR-selective ligands: LGD1069, LG100268, AGN194204, and LG101506, a selective RXR modulator. Similar to selective modulators of other nuclear receptors such as the estrogen receptor (SERMs), LG101506 binding to RXR selectively maintains the desirable characteristic effects of rexinoids while minimizing the undesirable effects. These recent findings suggest that, with continued research efforts, RXR-specific ligands with improved pharmacological profiles may eventually be available as additional treatment options for the current epidemic of obesity, insulin resistance, type 2 diabetes, and all of the associated metabolic sequelae.